2004
DOI: 10.1152/ajplung.00313.2002
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II and the fibroproliferative response to acute lung injury

Abstract: Angiotensin II (ANG II), generated by activation of local renin-angiotensin systems, is believed to play an important role in tissue repair and remodeling, in part via transforming growth factor-beta (TGF-beta). Angiotensin-converting enzyme (ACE) inhibitors have been shown to abrogate experimental lung injury via a number of potential mechanisms; however, the potentially fibroproliferative role for ANG II in the lung has not been characterized. We hypothesized that, after lung injury, ANG II would stimulate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
198
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(209 citation statements)
references
References 53 publications
6
198
1
4
Order By: Relevance
“…Several reports have promoted Losartan as inhibitor of fibrotic progression in the bleomycin model (Fang, Zhu, Hu, & Liu, 2002;Marshall et al, 2004;Molina-Molina et al, 2006), and a recent report confirmed these findings (Yao, Zhu, Zhao, & Lu, 2006). Losartan was given by daily gavage from day 0 to day 14 or to day 21.…”
Section: Losartanmentioning
confidence: 86%
See 2 more Smart Citations
“…Several reports have promoted Losartan as inhibitor of fibrotic progression in the bleomycin model (Fang, Zhu, Hu, & Liu, 2002;Marshall et al, 2004;Molina-Molina et al, 2006), and a recent report confirmed these findings (Yao, Zhu, Zhao, & Lu, 2006). Losartan was given by daily gavage from day 0 to day 14 or to day 21.…”
Section: Losartanmentioning
confidence: 86%
“…J. Wang, Giri, Hyde, & Nakashima, 1989), N-Acetylcysteine (Cortijo et al, 2001;Hagiwara, Ishii, & Kitamura, 2000;Mata et al, 2003;Serrano-Mollar et al, 2003;Shahzeidi, Sarnstrand, Jeffery, McAnulty, & Laurent, 1991;Yildirim et al, 2005), Vitamin E (Kilinc et al, 1993), Curcumin (Punithavathi, Venkatesan, & Babu, 2000), Aminoguanidine (X. L. Chen, Huang, Li, Wang, & Wang, 2001; X. L. Chen, Li, Zhou, Ai, & Huang, 2003;de Rezende, Martinez, Capelozzi, Simoes, & Beppu, 2000;Giri, Biring, Nguyen, Wang, & Hyde, 2002;Hu, Xu, & Li, 1999;Yildirim et al, 2004), Melatonin (Arslan, Zerin, Vural, & Coskun, 2002;Genovese, Di Paola et al, 2005;Yildirim et al, 2006), Bilirubin (H. D. , CAPE = caffeic acid phenethyl ester , Erdosteine (Boyaci et al, 2006;Sogut et al, 2004;Yildirim et al, 2005;Yildirim et al, 2004) etc. ), Angiotensin converting enzyme inhibitors (Captopril (R. Wang, Ibarra-Sunga, Verlinski, Pick, & Uhal, 2000), Ramipril (Marshall et al, 2004) etc. ), Angiotensin receptor blockers (Losartan (Fang, Zhu, Hu, & Liu, 2002;Marshall et al, 2004;Yao, Zhu, Zhao, & Lu, 2006), Candesartan (Otsuka, Takahashi, Shiratori, Chiba, & Abe, 2004), Valsartan (F. Liu, Xu, & Ye, 2005;Mancini & Khalil, 2005) etc.…”
Section: Drug Intervention Studies In the Bleomycin Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor termination of TGF␤1-mediated myofibroblast differentiation could contribute to chronic fibroproliferative disease and excessive scar formation in the injured lung, heart, liver, kidney, and skin potentially causing pathobiologic phenomena referred to as "endless healing" (Tomasek et al, 2002). In particular, pulmonary fibrosis typically is associated with chronic myofibroblast activation, deposition of interstitial collagen and SM␣A, and dysfunctional parenchymal remodeling with a mortality of 50% at 5 y after diagnosis (Zhang et al, 1996;Kunkel et al, 2003;Noble, 2003;Phan, 2003;Selman and Pardo, 2003;Daniels et al, 2004;Marshall et al, 2004;Willis et al, 2006;Wynn, 2007). Similarly, cardiac transplant chronic rejection is associated with pervasive interstitial myofibroblast accumulation and perivascular fibrosis that ultimately impairs heart graft perfusion, performance, and long-term survival (Weber, 1995; Armstrong et al, 1997a,b,c;Subramanian et al, 1998Subramanian et al, , 2002Rosenkranz, 2004).…”
mentioning
confidence: 99%
“…Glutamyl aminopeptidase is an enzyme that converts angiotensin II to angiotensin III. It is known that angiotensin II stimulates lung fibroblast proliferation through the activation of TGF-β (Marshall et al, 2000(Marshall et al, , 2004. The P2X receptor is strongly expressed in the pulmonary epithelium and endothelium.…”
Section: Discussionmentioning
confidence: 99%